Prognostic Implications of Change in Left Ventricular Ejection Fraction After Transcatheter Aortic Valve Implantation - Kuneman Jurrien H.; Butcher Steele C.; Singh Gurpreet K.; Wang Xu; Hirasawa Kensuke; van der Kley Frank; Leon Martin B.; Knuuti Juhani; Pibarot Philippe; Marsan Nina Ajmone; Delgado Victoria; Bax Jeroen J. (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2022)
Reduced left ventricular (LV) systolic function is associated with worse prognosis in patients with severe aortic stenosis (AS) treated with transcatheter aortic valve implantation (TAVI). We aimed to examine the changes in left ventricular ejection fraction (LVEF) after TAVI among patients with varying baseline LVEF. Moreover, variables associated with lack of LVEF improvement were identified and the association with long-term outcomes was investigated. A total of 560 patients (age 80 ± 7 years, 53% men) with severe AS who underwent transfemoral TAVI between 2007 and 2019 were selected. LVEF was assessed from transthoracic echocardiography at baseline (before TAVI) and at 6 and 12 months after TAVI. Patients were stratified according to baseline LVEF: (1) LVEF ≥50%, (2) LVEF 40% to 49%, and (3) LVEF <40%. The clinical end point was ≥5% LVEF improvement. The primary outcome was all-cause mortality. Patients with baseline LVEF<40% showed greater increase in LVEF than those with baseline LVEF 40% to 49% and LVEF ≥50% (from 33% ± 6% to 43% ± 10%, p <0.001; from 45% ± 3% to 52% ± 8%, p <0.001; and from 58% ± 5% to 59% ± 7%, p = 0.012, respectively, p for interaction <0.001). Coronary artery disease (odds ratio [OR] 1.80 [95% confidence interval (CI) 1.06 to 3.06], p = 0.031), myocardial infarction (OR 2.07 [95% CI 1.19 to 3.61], p = 0.010), and permanent pacemaker (OR: 1.93 [95% CI 1.25 to 3.00], p = 0.003) were independently associated with the lack of ≥5% LVEF improvement. During a median follow-up of 3.8 (interquartile range 2.6 to 5.2) years, 176 patients died (31%). Patients with ≥5% LVEF improvement had similar outcomes compared with those with <5% LVEF improvement (log-rank p = 0.89). In conclusion, patients with severe AS and baseline LVEF <40% had the greatest improvement in LVEF at 1-year follow-up after TAVI. Coronary artery disease, myocardial infarction, and permanent pacemaker were associated with lack of LVEF improvement. However, LVEF improvement at 12 months was not associated with long-term outcomes.